Reinventing Human Resource Practices Through Digital Marketing Platforms and Remote Work Technologies - Pramudito, Eko Sigit; Widayanti, Riya; Purnama, Suryari; Al-Farouqi, Kamal Arif (APTISI Transactions on Management (ATM), 2025)
The digital era has transformed human resource (HR) management, with or- ganizations adopting digital platforms, remote work technologies, and digital marketing strategies to improve productivity, optimize talent management, and enhance employer branding. These innovations also support Sustainable Devel- opment Goals (SDGs), including SDG 4 (Quality Education), SDG 8 (DecentWork and Economic Growth), and SDG 9 (Industry, Innovation, and Infrastructure). This study examines how HR practices are reinvented through dig- ital tools and marketing-driven initiatives, focusing on recruitment, employee engagement, performance management, and training, while highlighting chal- lenges and opportunities. A qualitative descriptive approach analyzed sec- ondary data from peer-reviewed journals, case studies of multinational corpora- tions and SMEs, and industry reports published between 2021 and 2025. Con- tent analysis identified themes related to HR digital adoption, workforce en- gagement, marketing integration, and strategic implications. HR digitalization poses challenges such as employee resistance, digital literacy gaps, cybersecu- rity risks, and maintaining organizational culture. Opportunities include greater flexibility, cost efficiency, improved engagement, enhanced employer branding, and access to global talent pools. Digital platforms, remote work, and marketing strategies are strategic assets reshaping HR management and aligning practices with sustainability goals.